Does accumulated family risk inhibit adolescent physical activity at home? An examination with a longitudinal latent growth model - Jingtao Wu; Yanhong Shao; Wennan Zhao; Wanli Zang; Xinjuan Zhao; Jun Hu (BMC Public Health)
Abstract Background The escalating prevalence of problem behaviors among adolescents, primarily stemming from accumulated family risk has emerged as a significant concern in contemporary school and family education. This phenomenon warrants particular attention as it may directly lead to reduced physical activity levels among adolescents within their domestic settings, potentially resulting in significant long-term consequences. Grounded in ecological systems theory, this study seeks to elucidate the cumulative effects of family risk on adolescent development. Through the application of a latent growth model across three distinct observation periods, we aim to systematically examine and clarify the longitudinal development trajectories and underlying interaction mechanisms of the variables under investigation. Methods A simple random cluster sampling method was utilized to select four middle schools from Sichuan Province, Guangdong Province, Hebei Province, and Beijing City as the research sites. A total of 682 primary and middle school students participated in three waves of follow-up surveys. Data were collected using validated scales, including the Accumulated Family Risk Scale and the Home Physical Activity Scale, to assess the respective constructs. Results (1) Adolescent accumulated family risk and home physical activity exhibited relative stability over the three observation periods, and a significant negative correlation was observed between these two variables. (2) The initial levels of adolescent home physical activity and accumulated family risk were significantly negatively correlated. Furthermore, these initial levels were found to significantly predict the growth rate of accumulated family risk, with the direction of influence being negative. Conclusion The findings suggest that higher levels of physical activity and lower initial levels of accumulated family risk may serve as protective factors against the escalation of accumulated family risk levels during adolescence. These findings offer novel empirical evidence and theoretical insights for designing targeted interventions aimed at mitigating accumulated family risks among adolescents.